Formation, conversion, and utilization of isorhodopsin, rhodopsin, and porphyropsin by rod photoreceptors in the Xenopus retina (The Rockefeller University Press, 1978)
The visual pigment content of rod photoreceptors in Xenopus larvae was reduced greater than 90% through a combination of vitamin A-deficient diet and constant light. Thereafter, a dose of either all-trans-retinol or 9-cis-retinal was injected intramuscularly, leading to the formation of a rhodopsin (lambdamax 504 nm) or isorhodopsin (lambdamax 487-493 nm) pigment, respectively. Electrophysiological measurements were made of the threshold and spectral sensitivity of the aspartate-isolated PIII (photoreceptoral) component of the electroretinogram. These measures established that either rhodopsin or isorhodopsin subserved visual transduction with the same efficiency as the 519 nm porphyropsin pigment encountered normally. When animals with rhodopsin or isorhodopsin were kept in darkness or placed on a cyclical lighting regimen for 8 days, retinal densitometry showed that either pigment was being converted to porphyropsin; significantly more porphyropsin was formed as a result of cyclical lighting than after complete darkness.